2019
DOI: 10.5114/jcb.2019.88116
|View full text |Cite
|
Sign up to set email alerts
|

Results from chemoradiotherapy for squamous cell cervical cancer with or without intracavitary brachytherapy

Abstract: Purpose: The aim of this study is to compare the outcomes of intracavitary high-dose-rate brachytherapy (BT-IC) boost and external beam radiotherapy (EBRT) boost in patients treated with concomitant chemoradiotherapy for squamous cell carcinoma of the cervix. Material and methods: It is a retrospective review of 92 patients with stage IB1-IVA cervical cancer treated with concomitant chemoradiotherapy between 2008 and 2013. All patients received pelvic 3D conformal EBRT (range, 45-50.4 Gy) concomitant with week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…SCCC is characterized by an aggressive disease course and poor prognosis, with a 5-year survival rate of only 29% compared to 68% in other cervical cancer subtypes. 1,21,22 In this study, the 1-, 3-, and 5-year OS were 63.3%, 36.9%, and 30.2% respectively. Consistent with the findings of previous studies, 8 we confirmed that the FIGO stage is an important prognostic indicator.…”
Section: Discussionsupporting
confidence: 47%
“…SCCC is characterized by an aggressive disease course and poor prognosis, with a 5-year survival rate of only 29% compared to 68% in other cervical cancer subtypes. 1,21,22 In this study, the 1-, 3-, and 5-year OS were 63.3%, 36.9%, and 30.2% respectively. Consistent with the findings of previous studies, 8 we confirmed that the FIGO stage is an important prognostic indicator.…”
Section: Discussionsupporting
confidence: 47%
“…Thus, an increased external pelvic dose will probably not compensate for exclusion of brachytherapy treatment. Prior studies have also confirmed the advantage of combined external and intracavitary therapy compared with external therapy alone [8,16,17]. The total dose (D90) to the HRCTV (external plus intracavitary) was significantly higher in the group treated with needles.…”
Section: Vaginal Toxicity (Only Recorded In the Igabt-group)mentioning
confidence: 80%
“…Over the past decade, very few studies evaluated the role of EBRT instead of BT boost. Due to old EBRT techniques delivering a suboptimal dose, and limited and different population studies, the results were almost disappointing (11)(12)(13).…”
Section: Cancer Diagnosis and Prognosismentioning
confidence: 99%